Reading comprehension and the development of critical thinking in primary education students - Mendoza Gonzales, Marita Esperanza (2025)
The purpose of this research was to analyze the relationship between reading comprehension and critical thinking among second-grade primary school students at a national educational institution. To this end, a balanced design was used, with a quantitative research approach and a hypothetical-deductive methodology. Two questionnaires on the variable(s) were administered to 91 students at Educational Institution No. 259, located in the Lurinchincha Population Center, Chincha Baja District, in 2024. The results revealed a positive classification of 0.62, obtained with Spearman's Rho coefficient, with a two-tailed significance level of 0.000. The descriptive analysis showed high levels in both competencies. It was concluded that the greater the development of reading comprehension, the higher the level of critical thinking, demonstrating that both skills are directly related in the context studied.